Clinical and Epidemiological Profile of Cardiovascular Disease at Rantauprapat Hospital, North Sumatra: A Retrospective Study - Shazni Nadia Reivana; Kartika Karo; Farida Hanum Margolang; Husnah (Faculty of Medicine, Hasanuddin University., 2026)
Introduction: Cardiovascular disease (CVD) is a leading cause of global mortality, with a significant and growing burden in Asia. Despite this, local epidemiological data in specific regions of Indonesia remain limited. This study aims to describe the clinical and epidemiological profile of patients with CVD at a regional hospital in North Sumatra, Indonesia. Methods: A retrospective, descriptive cross-sectional study was conducted using medical records from the cardiology outpatient clinic at Rantauprapat Hospital between January 1 and December 31, 2023. Data regarding patient age, sex, primary diagnosis, and comorbidities were extracted and analyzed descriptively. Results: A total of 2,116 patients met the inclusion criteria. The majority of the patients were male (52.69%), with the largest age group being 51–60 years (33.13%). Primary heart disorders constituted 70.04% of the cases, predominantly heart failure (65.97%). Coronary and peripheral vascular diseases accounted for 29.63% of the cases, primarily driven by coronary artery disease (23.49%). Additionally, hypertension was identified as the most prevalent concurrent comorbidity, affecting 35% of the study population. Conclusion: Heart failure and coronary artery disease are the most prevalent primary cardiovascular conditions among older adults at this regional hospital, significantly exacerbated by high rates of comorbid hypertension. These findings emphasize the urgent need for enhanced primary care interventions and targeted cardiovascular risk factor management within this population.